Twins for the neurosurgeon - Heaton, Louisa (Harlequin medical romance, 2021)
"Two tiny heartbeats... will change their lives forever! Top neurosurgeons Samantha Gordon and Yanis Baptiste spent one unforgettable night together in Paris. Their reunion in London proves even more explosive when they discover Sam is pregnant with twins! Neither Sam nor Yanis is prepared for parenthood, but those two tiny heartbeats could help them find the family neither of them believed they would ever have..." --